Role of doppler ultrasonography in predicting liver damage in alcololic patients - Coşar, Sumru; Coşar, Behçet (Journal of Dependence, 2005)
Alcoholism or ‘Alcohol Dependency’ as the name proposed by World Health Organisation (WHO) and American Psychiatric Association (APA) is the most common type of disorder related to substance abuse. Liver blood flow studies in alcoholic patients revealed varied data. Some authors defined increase in blood flow following ethanol intake while some others disagree. The etiopathogenesis of portal hypertension and hemodynamic effects of alcohol intoxication in alcoholic patients have not yet been clearly understood. The overall hemodynamic effect of the ethanol intake on splanchnic hemodynamics is an increase in portal and hepatic blood flow. However, a correlation between increased portal and hepatic blood flow, and portal hypertension could not be detected. This absence of correlation may suggests that besides increase in portal and hepatic blood flow, other mechanisms such as hepatic resistance are implicated in increased portal pressure. It is suggested that ethanol and its metabolites increase hepatic oxygen consumption, causing an increase in liver blood flow. Similarly, chronic alcohol consumption may be responsible from vasodilatation of hepatic artery in chronic alcohol dependent patients with no liver disease. In alcohol dependent patients possible pathologies expected to develop like cirrhosis, portal hypertension, or alcoholic hepatitis can be evaluated by ultrasound examination. However it is believed that some preliminary hemodynamic changes occur in alcohol dependent patients before these pathologies develop. Doppler Sonography is a non-invasive and reliable diagnostic tool in detecting hemodynamic changes.